Edge grinding device for steel plate cutting - ZHU HAILIN; WU JUN; FAN CHENBIN; ZHU ZHAODONG; MIAO SHENGLONG (2023)
The utility model relates to an edging device for steel plate cutting, which comprises a bottom plate, a fixing frame is arranged on the left side of the top of the bottom plate, a pressing piece is arranged at the upper end of the fixing frame, a steel plate fixing table and a rotating piece for controlling the steel plate fixing table to rotate are arranged at the upper end of the bottom plate, and a fixing plate is arranged on the right side of the top of the bottom plate. An adjustable edge grinding assembly is arranged on the fixing plate. According to the edge grinding device for steel plate cutting, a steel plate is placed on the steel plate fixing table, the steel plate is pressed and fixed through the pressing piece, the rotating piece can control the steel plate to rotate, in the edge grinding process, the edge grinding direction does not need to be manually adjusted, the side edge of the steel plate is controlled to be located between the two sets of grinding wheels through the first electric push